Mediation of buprenorphine analgesia by a combination of traditional and truncated mu opioid receptor splice variants. Issue 10 (12th July 2016) - Grinnell, Steven G.; Ansonoff, Michael; Marrone, Gina F.; Lu, Zhigang; Narayan, Ankita; Xu, Jin; Rossi, Grace; Majumdar, Susruta; Pan, Ying‐Xian; Bassoni, Daniel L.; Pintar, John; Pasternak, Gavril W.
Abstract: Buprenorphine has long been classified as a mu analgesic, although its high affinity for other opioid receptor classes and the orphanin FQ/nociceptin ORL1 receptor may contribute to its other actions. The current studies confirmed a mu mechanism for buprenorphine analgesia, implicating several subsets of mu receptor splice variants. Buprenorphine analgesia depended on the expression of both exon 1‐associated traditional full length 7 transmembrane (7TM) and exon 11‐associated truncated 6 transmembrane (6TM) MOR‐1 variants. In genetic models, disruption of delta, kappa1 or ORL1 receptors had no impact on buprenorphine analgesia, while loss of the traditional 7TM MOR‐1 variants in an exon 1 knockout (KO) mouse markedly lowered buprenorphine analgesia. Loss of the truncated 6TM variants in an exon 11 KO mouse totally eliminated buprenorphine analgesia. In distinction to analgesia, the inhibition of gastrointestinal transit and stimulation of locomotor activity were independent of truncated 6TM variants. Restoring expression of a 6TM variant with a lentivirus rescued buprenorphine analgesia in an exon 11 KO mouse that still expressed the 7TM variants. Despite a potent and robust stimulation of 35 S‐GTPγS binding in MOR‐1 expressing CHO cells, buprenorphine failed to recruit β‐arrestin‐2 binding at doses as high as 10 µM. Buprenorphine was an antagonist in DOR‐1 expressing cells and an inverse agonist in KOR‐1 cells. Buprenorphine analgesia is complex and requires multiple mu receptor splice variant classes but other actions may involve alternative receptors. Abstract : The mu opioid receptor gene Oprm1 undergoes alternative splicing to generate several sets of splice variants. Traditional 7TM Oprm1 variants mediate morphine actions. The current study shows that buprenorphine produces analgesia through a combination of 7TM and 6TM splice variants.